Penguatan Permodalan Koperasi dengan Skema Crowdfunding pada Koperasi ISM Karya Sinar Bahari, Desa Tanggul Jaya, Kelurahan Banten, Kecamatan Kasemen, Kota Serang, Provinsi Banten - Putra, Robi Nugraha Sayi; Sitohang, Veronica Lusianna; Pamuji, Bombong Ahmad; Kaban, Ira Caharina; Humaeroh, Fitri; Marjohan, Masno; Kasmad, Kasmad (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
The ISM Karya Sinar Bahari Cooperative, located in Tanggul Jaya Village, Banten, faces significant challenges in accessing adequate capital to sustain its green mussel aquaculture operations. This community service project explores the implementation of crowdfunding as an innovative solution to strengthen the cooperative's capital base. Through this initiative, cooperative members received intensive training on crowdfunding-based capital management. The study identifies the potential of crowdfunding to enhance the cooperative's financial capacity and assesses its impact on improving member welfare and the success of the aquaculture business. The findings demonstrate that this scheme successfully engaged member participation and diversified the cooperative's funding sources.